A Comparison of Experts' and Entrepreneurs' Opinions on International Business Activity - Gubik Sáfrány, Andrea (Theory, Methodology, Practice – Review of Business and Management, 2011)
Small and medium-sized enterprises often need external help in the process of internationalisation. This is usually an explicit pressure arising from their size and not a shortcoming. The objective of the present study is to learn the opinion of experts working in the fields of regional development and enterprise development who provide support for small and medium-sized enterprises in this field. Besides gaining insight into the opinions of professionals having first-hand information on the circumstances – barriers and motivations – of small and medium-sized enterprises (SMEs) to enter international markets, we will also discuss the views of managers on the issue based on a survey conducted in 2007. Based on the results of this survey, the majority of managers in international markets are satisfied with their own competencies, and tend to see the reasons for less successful international activities in external circumstances (strong competition, the lack of supportive system, etc.). The main objective of the second survey, conducted among experts is to provide objective insight into the circumstances of internationalisation and the prospects of small and medium sized enterprises.